Bibliography: hamas - Teiner, David (Perspectives on terrorism, 2021)
This bibliography contains books, edited volumes, journal articles, book chapters, theses, grey literature, and other resources on Ḥarakat al-Muqāwamah al-ʾIslāmiyyah, also referred to in short as Hamas. The publications compiled in this bibliography primarily focus on Hamas’ organizational evolution, its attacks, military successes and setbacks, recruitment efforts, ideology, and media outreach. Additionally, several studies examine Hamas’ role in Palestinian politics and forms of local governance. Furthermore, many of the included publications assess PVE and CVE strategies to contain Hamas’ political influence or evaluate the successes and shortcomings of peace and ceasefire negotiations with Hamas, as well as military and civilian campaigns against the organization.